Lysozyme in chronic liver disease: a biochemical and histological study. - Manifold, I H (1982)
Serum lysozyme activities and semiquantitative analysis of tissue lysozyme distribution were studied in patients with primary biliary cirrhosis (PBC), chronic hepatitis (CH), miscellaneous liver diseases, and normal subjects. Serum lysozyme was significantly raised in PBC and CH. Portal venous blood has similar lysozyme activities to peripheral venous blood in a group of various liver diseases. Lysozyme-containing intralobular cells were decreased in all liver diseases studied but portal tract lysozyme was increased only in PBC and CH. Thus the increase in serum lysozyme in PBC and CH appears to originate from the portal inflammatory infiltrate, seen in these diseases.